Renaissance [International Festival of Extra ordinary Textiles] (HS_Projets, 2014)
The second edition of the FITE has Renaissance as a main theme - the renaissance of peoples. It explores the idea of renewal. People with different points of view can discover each other, gather together and discuss in Clermont-Ferrand. The thoughts resulting from the cross-fertilization of diverse invaluable approaches are expressed in the symbolical places of the city, and in its cultural and heritage sites. The urban space which belongs to everybody is a space where relations and energies called up for the creation of the Festival can fully express themselves. As in 2012, the idea for the international edition of the FITE 2015 came up when we met the great Filipino fashion designer Patis Tesoro.